Sustainable strategic nation branding through sports: leveraging soft power via mega-event hosting - El-Dabt, Laila; AlReshaid, Faisal; Park, Kathleen; AlBuloushi, Nour; Al-Enzi, Abrar (Frontiers in Sociology, 2025)
IntroductionThis study examines the strategic management of nation branding from a soft power perspective, focusing on Qatar’s use of sports mega-events to enhance its global image. In contrast to hard power, soft power, in the realm of national or public diplomacy, refers to using cooperation rather than coercion to influence the impressions and preferences of others. Our research highlights the efforts by the government of Qatar to leverage sporting events, such as the FIFA World Cup, to boost international visibility, enhance cultural exchange, and attract tourism and investments.MethodsUsing document analysis and semi-structured interviews, we investigate how global sports serve as a unique soft power vehicle for nation branding, building the attraction and appeal of a nation.ResultsOur findings deepen insights into how nations can strategically and sustainably use globally known and popular sports to cultivate soft power, heighten national pride, and project a positive identity on the world stage.DiscussionWe contribute to the literature on soft power by developing a systematic conceptual framework for understanding how mega-sports events can be strategically managed to support nation branding and public diplomacy.